Correlation of Arterial Blood Gas Parameters with the Duration of Proning in Awake Non-intubated COVID-19 Patients- A Retrospective Observational Study - Roopali,; Agarwal, Ankit; Jain, Gaurav; Tripathy, Debendra K (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Prone positioning (PP), which has been known for decades to increase oxygenation in mechanically ventilated patients with moderate to severe acute respiratory distress syndrome (ARDS), was also practiced in Coronavirus disease (COVID-19) patients. We hypothesized that prone positioning in critically ill COVID-19 patients would improve oxygenation and ventilation and potentially translate into improved survival.Methods: A retrospective, observational study was conducted in All India Institute of Medical Sciences, Rishikesh, from March 2021 to July 2021. SARS- CoV-2 reverse transcriptase – polymerase chain reaction (RT-PCR) positive adult patients admitted to the ICU on non-invasive ventilation were included in the study. Proning durations were categorised as adequately proned (at least six hours/day), inadequately proned (four to six hours/ day) and minimally proned (less than four hours/ day). Results: The 30 included patients underwent 95 proning sessions. The change in PaCO2 had no statistically significant correlation with the duration of proning in hours (rho= -0.11, p = 0.295). There was a statistically significant weak positive correlation between the change in PaO2 and duration of proning in hours (rho = 0.22, p